2005
DOI: 10.1021/ef040088s
|View full text |Cite
|
Sign up to set email alerts
|

Radicals from the Pyrolysis of Tobacco

Abstract: The fractional pyrolysis of Bright tobacco was studied in an inert nitrogen environment at atmospheric pressure over a temperature range of 200-700 °C, using a continuous-flow reactor system. The effect of pyrolysis conditions on the generation of free radicals and their distribution among total particulate matter (TPM), char residue, and the gas phase was characterized using electron paramagnetic resonance (EPR) and EPR spin-trapping techniques. It was found that the fractional pyrolysis of tobacco led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 45 publications
5
60
0
1
Order By: Relevance
“…The gaseous products consisted largely of CO 2 in both SBOC and SFOC. This result is consistent with previous observations in that CO 2 is major gaseous product from the pyrolysis of biomass [21][22][23][24]. The amount of CO in pyrolysis gas products from SFOC was about two times higher than that of SBOC.…”
Section: Resultssupporting
confidence: 93%
“…The gaseous products consisted largely of CO 2 in both SBOC and SFOC. This result is consistent with previous observations in that CO 2 is major gaseous product from the pyrolysis of biomass [21][22][23][24]. The amount of CO in pyrolysis gas products from SFOC was about two times higher than that of SBOC.…”
Section: Resultssupporting
confidence: 93%
“…53,54 Despite different fuels, four studies examining combustion of catechol fuel, tobacco, and cellulose char pyrolysis consistently observed that concentrations of aromatic-structured, persistent free radicals peaked at a threshold temperature and then decreased with increasing combustion temperatures. [53][54][55][56] Figure 4 shows that under the full engine load, because the DEPs from the engine speed of 3000 rpm along with an exhaust temperature of 569°C (secondary x-axis) contained less persistent free radicals than that from the engine speed of 1800 rpm with an exhaust temperature of 497°C, the threshold temperature corresponding to the most abundant persistent free radicals would be lower than 569°C, resulting in the decreasing concentration of persistent free radicals with an increase in the exhaust temperature. Figure 5 shows that TPM was emitted from the individual driving conditions in a decreasing order of 3000 rpm/100% Ͼ 1800 rpm/100% Ͼ 3000 rpm/60% Ͼ 1800 rpm/60%.…”
Section: Persistent Free Radicals and Carbon Content In Depsmentioning
confidence: 99%
“…Secondly, there is a genuine difference in gas-phase composition on a puff-by-puff basis. [20][21][22][23][24][25] Literature shows that in aged smoke the concentration of the free radicals is unexpectedly increased; this has been explained by the radical reactions associated with NO and NO 2 . 10,18 More work is needed to address the contributions of these factors.…”
Section: Depmpo As Spin-trapmentioning
confidence: 99%